Quantum Dots: Single Halide Perovskite/Semiconductor Core/Shell Quantum Dots with Ultrastability and Nonblinking Properties (Adv. Sci. 18/2019). Issue 18 (18th September 2019) - Tang, Xiaosheng; Yang, Jie; Li, Shiqi; Liu, Zhengzheng; Hu, Zhiping; Hao, Jiongyue; Du, Juan; Leng, Yuxin; Qin, Haiyan; Lin, Xing; Lin, Yue; Tian, Yuxi; et al.
Abstract : In article number1900412, Juan Du, Yuxin Leng, Miao Zhou, and co‐workers successfully fabricate single CsPbBr3 /CdS core/shell structured quantum dots (QDs) by capping a CsPbBr3 QD core with a CdS shell. The core/shell QDs exhibit ultrahigh chemical stability and nonblinking photoluminescence. Furthermore, low threshold whispering‐gallery‐mode lasing with a high‐quality factor is achieved by incorporating CsPbBr3 /CdS QDs into microtubule resonators.